Appreciation and Enjoyment of Meaningful Entertainment : The Role of Mortality Salience and Search for Meaning in Life - Hofer, Matthias (Journal of Media Psychology, 2013)
Appreciation is an audience response associated with entertainment portrayals concerned with the meaning of life and human existence. Appreciation has been shown to be conceptually and empirically different from enjoyment, which is characterized as pleasure and fun. Drawing upon terror management theory, this research investigates first the influence of reminders of one’s own death on appreciation and enjoyment of a meaningful film and second, the influence of the search for meaning in one’s life on these outcomes. Results of an experimental study (N = 60) showed that mortality salience increased appreciation of a meaningful film, but only for those who rated highly for search for meaning in life. Concerning enjoyment, a reverse pattern was found: Participants who intensely search for meaning in their lives enjoyed the film when their own mortality had not been made salient before watching. Results are discussed in the light of theoretical considerations about entertainment experiences and meaning.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTAyNy8xODY0LTExMDUvYTAwMDA4OQ